Augmented Reality: New Approach in Distance Education Students’ Learning Process - Marisa Marisa; Suryo Prabowo; Bachriah Fatwa Dhini; Kristina Anugerah Aji (Universitas Terbuka, 2022)
The Educational Technology Study Program of Universitas Terbuka offers online practical courses. However, students face difficulties to complete their learning objectives in these courses. This study aims to provide appropriate media and adequate learning experiences for distance education students using augmented reality. Design of this study uses ADDIE model. Population of this study are students and tutors in 20 regional offices. The results showed that augmented reality media in online tutorials was quite effective in providing learning experiences. Augmented reality can bring reality into classroom for distance education students and assist them practice their courses. Even so, students still face obstacles in using the media, namely the incompatibility of student devices with the media, and minimum required tools to produce instructional video program. Therefore, a synchronous learning session between students and tutor is necessary.